Evaluation of the antimicrobial activity of Gooseberry and Wild Apple fruit juices of the northeast region of India - Punjabi, Kapil; Chitalia, Vidushi K.; Mukadam, Tehmeena; Sharma, Jaishankar; Maniar, Jinesh; Vasave, Shital; Vaidya, Shashikant; Dikho Mao, L. (Journal of Medicinal Herbs and Ethnomedicine, 2017)
A large number of wild fruits belonging to the North Eastern region of India are considered to be nutritionally abundant and traditionally used for the treatment of various ailments. In the present study, juices of Gooseberry and Wild Apple have been evaluated for their antimicrobial activity in its consumable form as a potential source of natural anti-infective agent. The fruit juices were screened for their antibacterial and antifungal activities qualitatively, using the agar well diffusion method followed by quantitative assessment by determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The study revealed that both the fruit juices exhibited broad spectrum antibacterial activity. Considerable activity against drug resistant pathogens such as Methicillin Resistant Staphylococcus aureus (MRSA), Vancomycin Resistant Enterococci (VRE) and Extended Spectrum ÃŽÂ²-Lactamases (ESBL) producing Gram Negative bacteria (GNB) was observed. Thus, this study highlights the antibacterial efficacy of Wild Apple and Gooseberry fruit juices and augments the beneficiary properties of highly nutritional fruit juices that are specific to the Indian region.